Analysis Of XXX Service Quality Using The E-Service Quality And Importance Performance Analysis - Aswarasy, Kardinna; Bernik, Merita (Dinasti International Journal of Economics, Finance & Accounting, 2024)
The trend of digital banking is growing with easy access through mobile banking such as XXX marked by performance that increases every year and is included in the most frequently used mobile banking. However, some users complain about XXX application problems related to the services provided, namely not being able to log in easily, requests cannot be processed, the application is very slow, and other problems. To solve this problem, XXX needs to improve the performance of the services provided. This study aims to determine the current service quality of XXX as well as the gap between customer perceptions and expectations and find out the attributes that are prioritized to improve service quality. The research method used is E-Service Quality with 6 variables, namely site organization, reliability, responsiveness, user friendliness, personal needs, and efficiency followed by the Importance Performance Analysis method through a quantitative approach. From the research results, it is found that the quality of XXX service provided is not yet qualified based on the level of conformity with an average value of 98% and the level of gap with an average value of -0.08 which explains that the current service quality is not in accordance with the quality expected by users. Then, the factors that need to be prioritized are statement items in quadrant concentrate here, namely Pages in the XXX app do not stop working suddenly, XXX app can be used immediately and runs smoothly, I can complete transactions quickly in the XXX app, XXX app provides services exactly at the time specified, and XXX app is easy to use.